2016
DOI: 10.1002/srin.201600086
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Microstructure and Properties of Steel 22MnB5 due to Short Austenitization with Subsequent Quenching

Abstract: In this work, the influence of rapid heat treatment with short low-temperature austenitization at different soaking temperatures on strength properties of tool-quenched low-carbon steel is presented. Two different modes of heat treatment for 22MnB5 have been carried out: conventional austenitization for 300 s at 950 8C and short austenitization for 2 s at soaking temperatures from 830 to 900 8C with subsequent quenching in watercooled dies. Subsequently, the mechanical properties of the heat-treated material h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…A microstructure consisting of ferrite, bainite, martensite and not completely dissolved carbides is formed during steel cooling. [18,26] Furthermore, alloying elements such as manganese or chromium reduce the critical cooling rate. In microscopically small areas where high amounts of these alloying elements are present, for example around dissolved carbides, martensite is formed.…”
Section: B Micrograph and Hardness Investigationsmentioning
confidence: 99%
“…A microstructure consisting of ferrite, bainite, martensite and not completely dissolved carbides is formed during steel cooling. [18,26] Furthermore, alloying elements such as manganese or chromium reduce the critical cooling rate. In microscopically small areas where high amounts of these alloying elements are present, for example around dissolved carbides, martensite is formed.…”
Section: B Micrograph and Hardness Investigationsmentioning
confidence: 99%
“…One disadvantage of this method is high energy expenses ( Ref 16). Furthermore, it is possible to use alternative heating processes that ensure high heating rates and low oxidation, such as inductive ( Ref 17,18), conductive (Ref 18,19) and contact (Ref 20,21) heating. However, these might be disadvantageous due to extensive equipment, non-uniformity of heating or the necessity to use uncoated sheets.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported by Karthikeyan et al [ 3 ] that the grain size of 9Cr-1Mo steel was refined from 26 to 12 μm via high temperature holdings. The grain size of 22MnB5 carbon steel was significantly refined by short austenization at 900 °C for 2 s, and the tensile properties and hardness were greatly enhanced [ 4 ], whereas, high temperature holdings for a long period of time could lead to grain coarsening of steels. Fernández et al [ 5 ] carried out research on grain size evolution of 16MnNi4 steel in isothermal holdings via metallography, and it showed that the dramatic growth of grains was followed by a slow growth during holding at 1050–300 °C.…”
Section: Introductionmentioning
confidence: 99%